Uruguay : Financial Sector Review - World Bank (Washington, DC, 2013)
The study reviews Uruguay's financial sector, identifying a well-developed banking sector, which reflects off-shore banking growth stimulated by regional macroeconomic instability, and by the country's strict national banking laws. By contrast, the country's capital market is underdeveloped, with a market capitalization of less than one percent of GDP, compared to the average ten percent in emerging markets. Similarly, the contractual savings sector, including pension/mutual funds, and insurance companies, is highly incipient. The small open economy has significant implications for its financial sector strategy, since its domestic economy is not large enough to sustain a domestic financial sector, particularly considering increased border trade in financial services, via electronic banking, and securities trading. Thus, its alternative may be to become highly competitive in banking services, including exporting these services. Based on substantiated evidence, it is suggested that the comparative advantage of Uruguayan banks is gradually eroding, but should it become competitive, the country could export some banking services, provided it explores setting up a regional stock exchange within MERCOSUR, which may well improve liquidity, rather than revive local exchanges; improve the constrained private participation (resulting from a preponderant State role); and, strengthen regulatory, and supervisory framework.